Mapping the Situation of Educational Technologies in the Spanish University System Using Social Network Analysis and Visualization - Vargas Quesada, B.; Zarco, Carmen; Cordón, Oscar (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2023)
Educational Technologies (EdTech) are based on the use of Information and Communication Technologies (ICT) to improve the quality of teaching and learning. EdTech is experiencing great development at different educational levels worldwide, especially since the appearance of Covid-19. The recent publication of a study by the ICT Sectorial of CRUE Universidades Españolas, the Spanish University Association, is the first report on the implementation of such technologies within Spain´s University System. This paper presents two different maps based on the data from that report. Together, they illustrate the penetration of different types of EdTech in our university system and shed light on the strategic interest behind their adoption. Our goal is to produce self-explanatory maps that can be easily and directly interpreted. The first map reflects wide granularity in terms of the global importance of technologies, while the second points to relevant conclusions given the spatial position of Spain´s universities, and the size of the nodes that represent them (directly related with their strategic interests on EdTech), as well as with the local relationships existing among them (identifying similarities on those strategic interests).
Keywords: education; information technology; social network analysis; maps; universities; IJIMAI; Scopus; JCR